STRATEGI PEMASARAN PADA BANK PEMERINTAH: STUDI KASUS PT. BANK MANDIRI Tbk. CABANG YOGYAKARTA TAHUN 2004 - Toga Sehat Sihite; Vitri Tarigan; Marintan Saragih; Robert Tua Siregar (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2020)
Marketing strategy as an important aspect to maintain and expand opportunities to reach the market. Studies that explore the Bank's internal marketing strategies have been examined by previous research but based on competitive banking dynamics and highly dynamic market demands it is difficult to predict, the study of marketing strategies in the context of the Bank's companies is considered to be relevant for review at any time. This article aims to analyze the marketing strategies available at PT Bank Mandiri, Tbk Yogyakarta branch 2004 with the SWOT analysis method. Data was obtained through interviews with the management of the Bank Mandiri Yogyakarta branch. The analytical tool used is the analysis of industrial structure (Porter), SWOT. The results of the study through a SWOT analysis of the position of PT. Bank Mandiri in its marketing strategy uses a growth strategy.